The influence of the physical features on users' attachment to KLCC Park, Malaysia - Ayeghi, Atefehalsadat (2013)
Parks are perceived as an important part of the quality of life in densely populated urban areas (Harnik 2000). As Malaysia becomes more urbanized since the 90’s, the need for recreational areas has been increasing. Based on the Kuala Lumpur Structure Plan 2020, recreational areas are growing as one of the most essential areas in the city However,as opposed to recreational areas in the western world, urban recreational areas in Malaysia have obtained very little attention from researchers, the reason being that Malaysia only has a short public parks tradition. The reason goes back to 1874, when British colonized Malaysia whereby throughout that period gardens and other forms of parks existed only for members of the royal families, this led public to be unfamiliar with such spaces (Mohamed & Nawawi, 2006). The main objective of the present study is to identify the influence of physical feature on the usability of an urban park which will result in users’ attachment to the park. KLCC Park was selected for this study because it is an important landmark for Kuala Lumpur city, and one that represents internationally the ‘greenness’ of the city. These make the KLCC Park as a major point of interest to locals and foreign tourists. Thus, it is essential to ensure continued visits that will increase usability of the park. The study adopted a quantitative method to determine the impact of physical features on users’ needs in KLCC Park. To gain preliminary information on the topic, in-depth interviews with Kuala Lumpur City Hall Public Park managers were conducted to understand the current issues regarding urban parks in Malaysia, specifically in Kuala Lumpur. Casual observation was used to identify the physical features of KLCC Park and also to observe subjects prior to designing the questionnaire. The questionnaire survey was conducted with 330 park users to identify the influence of physical features on users’ needs in KLCC Park. The participants were selected randomly from those who use the park. The data were analyzed using SPSS version 19.0. In order to achieve the objectives of the study as well as testing the hypothesis of this research, correlation and regression analyzes was carried out. The research found that physical features influence the usability of the park. In addition, hardscape features such as water features had a strong effect onusers’ passive engagement needs. The results highlight the importance of water features in fulfilling user’ comfort and relaxation needs. The findings will assist urban managers and urban designers to better understand the importance of specific physical features in creating more attractive places for users.